Development of Interactive Radio for Scaling Market-oriented Sheep Fattening in Ethiopia - Ekule, Muluken; Wamatu, Jane (International Center for Agricultural Research in the Dry Areas, 2022)
A training report for development of interactive radio for scaling market-oriented sheep fattening in Ethiopia